211k views
2 votes
If a = -2, b = -6, c = -4, and d = -3, evaluate the following expression

A. -12

B. 0

C. -3

D. 3

If a = -2, b = -6, c = -4, and d = -3, evaluate the following expression A. -12 B-example-1
User Scgough
by
6.2k points

2 Answers

4 votes

Answer:

_6-(-4x-3)/-2

-6-(-12)/-2

-6+12/-2

-6+6

=0

User Austin Pocus
by
5.8k points
0 votes

Answer:

B. 0

Explanation:

a = -2, b = -6, c = -4, and d = -3,

b-cd/a

-6-(-4*-3/-2)

-6-(12/-2)

-6-(-6)

-6+6

= 0

User Lalithkumar
by
5.8k points